Study the effects of Cloisite15A nanoclay incorporation on the morphology and gas permeation properties of Pebax2533 polymer. Issue 37 (4th June 2017) - Behroozi, Maryam; Pakizeh, Majid
ABSTRACT: In this study, mixed matrix membranes (MMMs) were prepared using commercially available poly(ether‐ b ‐amide) (Pebax2533) as polymer matrix and organically modified montmorillonite (OMMt) as filler with the aim of investigating their gas permeation properties. The prepared membranes were characterized by Fourier‐transform infrared (FTIR) spectroscopy, X‐ray diffraction (XRD), scanning electron microscope (SEM), thermal gravimetric analysis, and tensile strength analyses. Gas permeation properties of all the prepared membranes were evaluated at different pressures and clay loadings. Results of FTIR and SEM confirmed the appropriate adhesion between polymer and nanoclays so that no void formation was observed in the polymer/clay interface. XRD results showed that in low loading, clay dispersion occurred as exfoliated‐intercalated and at high loading as intercalated‐phase separated. Results of gas permeation test showed that by adding layered and impermeable clay particles to the polymer matrix, the permeation of soluble CO2 gas reduced by 28% for the highest clay loading. By increasing of pressure from 2 to 6 bar, CO2 /CH4 permselectivity increased at all nanoclay loadings. The highest CO2 /CH4 selectivity was obtained for 6 wt % clay MMM at all pressures, while the highest CO2 /H2 selectivity was achieved for neat polymer at 6 bar. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45302. Abstract :